Relationship between age, category and experience with the soccer referee’s self-efficacy - López Aguilar, José; Castillo-Rodriguez, Alfonso; Chinchilla-Minguet, José L.; Onetti-Onetti, Wanesa (PeerJ, 2021)
Soccer referees (SRs) encounter stressful situations during competitions and sometimes even outside them, which may affect their decision making. Therefore, it is important that they possess or acquire optimal levels of self-efficacy, since it is related to less stress during competition, also guaranteeing sports performance and prevent sports abandonment. The objectives of this study were to characterize the profile, in terms of self-efficacy, of SRs depending on their category, age, and experience and to determine the relationship of these factors on SR self-efficacy. Two-hundred fifty-six Spanish referees participated in this study and Referee Self-Efficacy Scale was administered and completed. The results indicated that the SRs older than 25 years, of national category, and with experience greater than or equal to 8 years, have higher levels of self-efficacy than those with the least (p < .01). Likewise, moderate positive correlations were also observed between global self-efficacy and the category, age, and experience of the SRs. In conclusion, age, category and experience factors relate the self-efficacy of the SR, which can explain up to 17% of the variance, affecting decision-making and other decisive behaviors in the competition. These findings are of interest to delegations and referee committees seeking to implement psychological intervention programs to prevent burnout and abandonment of sports practice due to the consequences of low self-efficacy.
Keywords: Decision making; Pressure; Personality; Competition; Football; Referee Self-Efficacy Scale